The role of executive functions and ICTs in anxiety management of children with ASD - Zografou, Maria; Stathopoulou, Agathi (Eximia, 2022)
The role of executive dysfunction in autism spectrum disorders (ASD) is critical for guiding diagnosis and intervention. Autism spectrum disorder (ASD) is a neurodevelopmental disorder defined by deficits in social communication and interaction and restricted and repetitive patterns of behavior. Evidence show that ICTs contribute to the reduction of stress in children with ASD because of their adaptive, playful and predictable digital environment. Mobile apps and robots have been found to work beneficially by helping with stressful situations.